The evolution of laughter in great apes and humans - Ross, Marina Davila (Landes Bioscience, 2010)
It has long been claimed that human emotional expressions, such as laughter, have evolved from nonhuman displays. The aim of the current study was to test this prediction by conducting acoustic and phylogenetic analyses based on the acoustics of tickle-induced vocalizations of orangutans, gorillas, chimpanzees, bonobos and humans. Results revealed both important similarities and differences among the various species’ vocalizations, with the phylogenetic tree reconstructed based on these acoustic data matching the well-established genetic relationships of great apes and humans. These outcomes provide evidence of a common phylogenetic origin of tickle-induced vocalizations in these taxa, which can therefore be termed “laughter” across all five species. Results are consistent with the claims of phylogenetic continuity of emotional expressions. Together with observations made on the use of laughter in great apes and humans, findings of this study further indicate that there were two main periods of selection-driven evolutionary change in laughter within the Hominidae, to a smaller degree, among the great apes and, most distinctively, after the separation of hominins from the last common ancestor with chimpanzees and bonobos.